A TWO-YEAR STUDY OF CANCEROGENIC POTENTIAL OF THE NEW OPIOID RECEPTOR ANTAGONIST ONDELOPRAN IN RATS - K. L. Kryshen; A. A. Muzhikyan; D. S. Gaidai; K. O. Zaikin; A. E. Katelnikova; M. Yu. Samsonov; E. I. Mukhametshina; G. E. Konopleva; E. V. Shipaeva; A. A. Dmitrieva; F. S. Shagiakhmetov; A. O. Popova; et al. (Исследования и практика в медицине)
Opioid receptor antagonists are widely used for the treatment of alcohol dependence. Currently, original drug Odelepran (INN: ondelopran) with a unique binding proﬁ le to all three types of human opioid receptors (μ, κ, δ) is being developed by R-Pharm.Aim of the study. To investigate a cancerogenic potential of the new opioid receptor antagonist ondelopran in a twoyear study in ratsMaterials and methods. The study cancerogenic potencial was performed in male and female Wistar rats at the age of 8–10 weeks at the start of experiment. All animals were allocated to 8 groups. Each group consisted of 50 animals of each sex. Test item (ondelopran ﬁ lm-coated tablets, 125 mg), was administered to the animals intragastrically as a tablets suspension in 1% starch solution daily, 5 days a week for 24 months in two doses: 10 mg/kg (equivalent therapeutic dose for humans) and 100 mg/kg. Animals of control groups were administered with placebo and vehicle (1% starch solution). Clinical observation and examination of animals were conducted weekly to detect any signs of intoxication; dynamics of the body weight and registration of animal deaths were also assessed. To assess the rate of the pathological changes, the macro- and microscopic examination of inner organs and neoplasms was conducted.Results. During the study the mortality rates did not diﬀ er between the groups. Clinical signs ts.and symptoms of intoxication upon administration of the tested item and placebo were not observed. Neoplasms were found in the organs of all groups of animals. More than 30 variants of neoplasms were identiﬁ ed upon pathomorphological examination. The identiﬁ ed tumors are typical for rats and considered as spontaneous age-related pathology. There was no statistically signiﬁ cant diﬀ erences between groups in the total incidence of tumors.Conclusion. To conclude the above said, the test item of the ondelopran ﬁ lm-coated tablets, 125 mg have no carcinogenic properties.